Quantity Discrimination in Trained Lizards (Podarcis sicula) - Miletto Petrazzini, Maria Elena; Bertolucci, Cristiano; Foà, Augusto (Frontiers in Psychology, 2018)
Quantitative abilities have been reported in many animal species. Two main methods have been extensively used: spontaneous choice tests and training procedures. A recent study showed that ruin lizards are capable of spontaneously discriminating between the surface area of two food items of different size, but failed when food was presented in sets of discrete items differing in number. In the present study we used a training procedure to further investigate quantitative abilities in ruin lizards. subjects were presented with two sets of yellow discs differing either in number (Experiment 1) or in area (Experiment 2) and were trained on different discrimination of increasing difficulty (1 vs. 4, 2 vs. 4 and 2 vs. 3). Results showed that lizards were more accurate in discriminating sets of discrete items differing in number than the area of two individual items, in contrast to what had earlier been observed in spontaneous choice tests. Although we cannot exclude other factors that affected the performance of ruin lizards, the poor accuracy here observed in both experiments might reflect a true limit in lizards’ quantitative abilities.